COGNITIVE ANALYSIS OF IDENTITY AND PERCEPTION IN THE PRINCE AND THE DRESSMAKER AND STARGAZING BY JEN WANG - Yunusova Nilufar Axmurodovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article examines the cognitive dimensions of identity formation, perception, and emotional development in The Prince and the Dressmaker (2018) and Stargazing (2019) by Jen Wang. Drawing on cognitive literary theory, the study explores how characters construct their identities, interpret social expectations, and develop empathy through interpersonal relationships. The analysis demonstrates that both graphic novels portray cognition as a dynamic process shaped by internal desires and external pressures. While The Prince and the Dressmaker focuses on the integration of conflicting identity schemes, Stargazing emphasizes the development of empathy and the role of imagination in cognitive growth.Cognitive literary criticism offers a valuable framework for understanding how fictional characters think, feel, and interpret the world around them. In the context of graphic novels, cognition is conveyed not only through language but also through visual representation, making the genre particularly effective in depicting internal psychological processes. Jen Wang’s works are especially significant in this regard, as they explore complex emotional and cognitive experiences through accessible narratives and expressive imagery.